Testament [videorecording (Blu-Ray)] - Young, John Sacret, 1946-2021; Alexander, Jane, 1939-; Devane, William, 1939-; Harris, Rossie, 1969-; Haas, Lukas, 1976-; Amen, Carol, 1933- (Criterion collection, 2026)
"It is just another day in the small town of Hamlin until something disastrous happens. Suddenly, news breaks that a series of nuclear warheads has been dropped along the Eastern Seaboard and, more locally, in California. As people begin coping with the devastating aftermath of the attacks -- many suffer radiation poisoning -- the Wetherly family tries to survive. Led by mom Carol (Jane Alexander), the clan tries to support each other even as they take in other stranded survivors." -- Rottentomatoes.com, March 6, 2026.